2011
DOI: 10.1039/c0ob00975j
|View full text |Cite
|
Sign up to set email alerts
|

The stimulating adventure of KRN 7000

Abstract: Associated with the CD1d protein, KRN 7000, a potent synthetic α-galactosylceramide, is known to activate the invariant NKT immune cells. This stimulation then leads to the production of different cytokines modulating a T(H)1/T(H)2 immune response balance involved in protection against several pathologies such as autoimmune diseases and cancers. Various efforts have been made toward the synthesis of simple and more functionalized analogues in order to selectively induce T(H)1 or T(H)2-type cytokine production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
123
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 203 publications
1
123
0
Order By: Relevance
“…[6][7][8]13,23 Previous structural alterations of the α-GalCer fatty acid chain have focused on modulating the hydrophobic interactions. Our ω-hydroxy α-GalCer analogue represents the first example that introduces a hydrogen bonding interaction within the binding groove of the A′ pocket.…”
mentioning
confidence: 99%
“…[6][7][8]13,23 Previous structural alterations of the α-GalCer fatty acid chain have focused on modulating the hydrophobic interactions. Our ω-hydroxy α-GalCer analogue represents the first example that introduces a hydrogen bonding interaction within the binding groove of the A′ pocket.…”
mentioning
confidence: 99%
“…This lipid binding orientation allows the sugar headgroup to be exposed in the center for recognition by the type I NKT cell TCR, with the ␣ chain of the TCR providing the predominant binding energy (8,9). Many GSLs have been analyzed for the activation of type I NKT cell TCRs, but the most commonly studied is ␣-galactosylceramide (␣GalCer) (10,11). This prototypical glycolipid activates type I NKT cells to secrete both IL-4 and IFN-␥ in vivo within 90 min.…”
Section: Natural Killer T (Nkt)mentioning
confidence: 99%
“…11−15 However, the in vivo efficacy of 1 has been somewhat limited because of its dual antagonizing effects on both Th1 and Th2 cytokines, and these dual effects are known to be polar opposites in immune response. 1 In other words, 1 can stimulate the secretion of both pro-and anti-inflammatory cytokines and can result in no net changes in immunity. Thus, many recent studies have focused on the synthesis of KRN7000 analogues that can selectively activate iNKT cells to secrete certain cytokines.…”
mentioning
confidence: 99%
“…Thus, many recent studies have focused on the synthesis of KRN7000 analogues that can selectively activate iNKT cells to secrete certain cytokines. 1 For example, the structural modification of the sugar moiety in α-GalCer revealed that the α-anomeric galactose is considerably better than other sugars, such as glucose, mannose, and β-galactose without selectivity. 12 However, the structural modification at the C6 position of the galactosyl moiety in α-GalCer with a 4Cl-3CF 3 -benzamide substituent (2) showed a promising Th1-based polarizing effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation